The influence of a Healthy Welcoming Environment on participation in club sport by adolescent girls: a longitudinal study - M. M. Casey; R. M. Eime; J. T. Harvey; N. A. Sawyer; M. J. Craike; C. M. Symons; W. R. Payne (BMC, 2017)
Abstract Background This study investigated the perceived influence of a Healthy Welcoming Environment (HWE) on participation in sports clubs among adolescent girls, and how these perceptions changed longitudinally. HWE was defined in terms of a set of health promotion policies advocated by a health promotion foundation as the basis of sport club health promotion practice to promote structural reform in state sporting organisations and their affiliated associations and clubs. These included sports injury prevention, smoke-free, responsible serving of alcohol, sun protection, healthy eating, and welcoming and inclusive environments. Methods Year 7 and 11 female students from metropolitan (n = 17) and non-metropolitan secondary schools (n = 14) in Australia were invited to participate in three annual surveys. These surveys collected information about current or past membership of a sports club and the influence of HWEs on their decision to participate (or not) in a sports club. Results Year 7 (n = 328; 74.5%) and Year 11 (n = 112; 25.5%) female students completed all three waves (19.6% response rate; 82.7 and 74.0% retention rate). Most agreed that characteristics of HWEs were a positive influence on their participation in sports clubs, except those relating to alcohol and Sunsmart. Welcoming factors had consistent high agreement among respondents. Alcohol and friendliness factors of the club were regarded as being positively influential by higher percentages of non-metropolitan than metropolitan respondents. Conclusions Welcoming factors were the most positive influences on decisions to participate in sports clubs. These factors may be important in reducing barriers to sport participation. Strategies supporting the social environment within sports clubs should be prioritised.